Inovasi Wakaf di Era Digital dalam Mengoptimalkan Potensi untuk Pembangunan Berkelanjutan di Negeri Berkembang - Nuradi; Nurul Huda; Husnul Khatimah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The concept of waqf, or Islamic philanthropy, has a long history in Indonesia, playing a significant role in the development of Muslim communities. Recent innovations in the digital era have opened up new opportunities for optimizing waqf management and its potential for supporting sustainable development in developing countries. This qualitative study aims to explore the role of digital waqf innovations in maximizing the potential for sustainable development in Indonesia, a developing country with the world's largest Muslim population. Through a comprehensive literature review and analysis of various journal articles, books, and other relevant sources, this research examines the practices of digital waqf innovations in developing countries. The findings highlight the potential of digital waqf innovations, such as crowdfunding, blockchain technology, and mobile applications, to enhance the efficiency, accountability, and reach of waqf management. These technologies can expand the collection of waqf funds, increase transparency, and facilitate easier access for the public to participate in waqf. Additionally, data analytics can be utilized to identify community needs and allocate waqf assets more effectively to support sustainable economic programs. However, challenges such as the need for increased digital literacy, public trust in digital waqf management, and the alignment of waqf regulations with digital technology advancements must be addressed. This study provides insights and recommendations for stakeholders in developing countries, particularly Indonesia, to harness digital waqf innovations for more optimal support of sustainable development programs.